Grouping оf Complexes оf Multiphase Queuing Systems - Zholtkevych, G.M.; Nazyrov, Z.F.; Ignatov, S.Y. (Journal of Information Technologies in Education (ITE), 2009)
Issues of classification of the complexes of multiphase queuing system systems in correspondence with entrance-output correlations and automatic grouping of complexes by the analysis of the graph of final product composition is examined in this work.